2014
DOI: 10.1155/2014/747584
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Extracellular Matrix Components in Cutaneous Wound Healing

Abstract: Wound healing is the physiologic response to tissue trauma proceeding as a complex pathway of biochemical reactions and cellular events, secreted growth factors, and cytokines. Extracellular matrix constituents are essential components of the wound repair phenomenon. Firstly, they create a provisional matrix, providing a structural integrity of matrix during each stage of healing process. Secondly, matrix molecules regulate cellular functions, mediate the cell-cell and cell-matrix interactions, and serve as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
291
0
42

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(334 citation statements)
references
References 87 publications
(178 reference statements)
1
291
0
42
Order By: Relevance
“…It is a secreted serine protease that converts the proenzyme plasminogen to plasmin and plays a critical role in cell migration and tissue remodeling. Keratinocytes use plasmin activated by plasminogen activators for paving their way through phase of the wound-healing process (47), and its inhibition, as seen in our study and also reported by others (34,48), is one of the main reason for the delay in wound closure. Ctgf and transforming growth factor b1 (Tgfb1) were significantly upregulated.…”
Section: Resultssupporting
confidence: 86%
“…It is a secreted serine protease that converts the proenzyme plasminogen to plasmin and plays a critical role in cell migration and tissue remodeling. Keratinocytes use plasmin activated by plasminogen activators for paving their way through phase of the wound-healing process (47), and its inhibition, as seen in our study and also reported by others (34,48), is one of the main reason for the delay in wound closure. Ctgf and transforming growth factor b1 (Tgfb1) were significantly upregulated.…”
Section: Resultssupporting
confidence: 86%
“…Triolein is a major form of triglyceride in human skin, which presents as subcutaneous fat and epidermal surface lipid. The apparent decrease in triolein as cancer progresses could be due to: (1) the reduction of subcutaneous fat sampled by the probe, caused by the thickening epidermis during lesion formation; and/or (2) the reduction of membrane lipid synthesis induced by UV damage [34]. Because subcutaneous fat exists in a substantial amount and has large Raman scattering cross section [41] we believe (1) is the major reason.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen fibers account for about 70% of the weight of dry dermis, while elastin maintains skin elasticity through a durable cross-linked array. Large diameter elastin-rich elastic fibers reside in the reticular dermis [34]. Figure 4 illustrates Raman imaging performed on a BCC skin section to extract dermal ECM proteins.…”
Section: Dermal Ecmmentioning
confidence: 99%
“…Interface with ECM components is regulated by mediators such as cytokines and growth factors (e.g. interleukins, interferons and TNF-α) (Olczyk et al 2014). The inflammatory response is triggered, and components such as growth factors facilitate proliferation, differentiation and metabolism of cells involved in the healing process.…”
Section: Wound Carementioning
confidence: 99%
“…The inflammatory response is triggered, and components such as growth factors facilitate proliferation, differentiation and metabolism of cells involved in the healing process. Others help regulate inflammatory processes and play a chemotactic role (encouraging cell movement) for neutrophils, macrophages, fibroblasts and epithelial cells (keratinocytes) to stimulate angiogenesis and the formation of ECM (Olczyk et al 2014).…”
Section: Wound Carementioning
confidence: 99%